Pengaruh Dewan Direksi, Dewan Komisaris Independen, Komite Audit, Profitabilitas, Dan Ukuran Perusahaan Terhadap Pengungkapan Sustainability Report (Studi Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Tahun 2017) Pengaruh Dewan Direksi - Faizah Naila Sofa; Novita WeningTyas Respati (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2020)
The topics of this research is the disclosure of sustainability reports. The topics of this research is the disclosure of sustainability reports.This study aims to determine board of directors, independent board of commissioners, audit committee, profitability, and firm’s size on the sustainability report disclosure in manufacture companies listed in IDX period 2017. Sustainability report disclosure are measured by using indeks global reporting initiative (GRI). The sample is determined based on purposive sampling method, this totaling 85 companies. The data used in this research is secondary data. Analysis technique of data is multiple linear regression. The result showed that the independent board of commissioners, audit committee, and profitability does not influential positive on the extent of sustainability report whereas the board of directors and firm size has influential positive on the extent of sustainability report. The result of this study also showed that the companies expected to disclose the sustainability report through the meeting of the board of directors and do disclosure in accordance with index GRI.